2015
DOI: 10.1055/s-0041-107764
|View full text |Cite
|
Sign up to set email alerts
|

Management of Intrauterine Arteriovenous Malformation (AVM) in 14 Patients by Sonographically Guided Tisseel Application

Abstract: In PPH there is vital interest in timely diagnosis of the underlying cause, thus allowing fertility-sparing, minimally invasive and super-selective emergency treatment. In AVMs causing PPH, a positive impact on perinatal morbidity and mortality may be achieved by sonographically guided application of this biological glue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Even in the cases we reported, imaging allowed the detection of the presence of a hypervascularized area in a hypoechoic myometrial area, with high multidirectional flow velocity and low vascular resistance. In AVMs, a direct communication is created between an artery and a vein (arteriovenous fistula) [3] , [39] , [40] , [41] , [42] ( Table 1 ), which some authors describe as a "color mosaic" model in which a low-resistance/high-velocity flow pattern is found in the abnormal vessels [43] , [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Even in the cases we reported, imaging allowed the detection of the presence of a hypervascularized area in a hypoechoic myometrial area, with high multidirectional flow velocity and low vascular resistance. In AVMs, a direct communication is created between an artery and a vein (arteriovenous fistula) [3] , [39] , [40] , [41] , [42] ( Table 1 ), which some authors describe as a "color mosaic" model in which a low-resistance/high-velocity flow pattern is found in the abnormal vessels [43] , [44] .…”
Section: Discussionmentioning
confidence: 99%
“…2 Pseudoaneurysms accompanying uterine arteriovenous malformations and cesarean scar pregnancy have also been rarely reported, possibly occurring due to placental invasion or high flow alterations. 3,4 Pseudoaneurysms differ from true aneurysms because the pseudoaneurysm wall has only thin adventitial tissue and is prone to rupture. These tend to increase in size slowly, and the rupture could be triggered by trivial trauma or pressure changes.…”
Section: Discussionmentioning
confidence: 99%
“…15 In gynaecology, two cases of UAP after a caesarean section were successfully treated by UGTI, 4 one percutaneous and another transvaginally guided. Moreover, two studies have recently reported the use of UGTI to treat post-partum haemorrhage due to intrauterine arteriovenous malformations, 5 as well as to treat caesarean scar pregnancies. 6 The management protocol was very similar to ours, injecting a human fibrin sealant (Tisseel®) allowing selective occlusion of the feeding vessels.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of gynaecology, UGTI was firstly described to treat two cases of late post-partum haemorrhage attributed to pelvic arterial pseudoaneurysm following caesarean section. 4 This technique has recently been used to treat haemorrhage due to intrauterine arteriovenous malformations during post-partum 5 and in caesarean scar pregnancies. 6…”
Section: Introductionmentioning
confidence: 99%